Perencanaan lanskap ekowisata di lahan carik Desa Cibodas Bandung, Provinsi Jawa Barat - Hayati, Munira; Fitri, Rini; Fauzi, Reza (Jurnal Arsitektur Lansekap, 2026)
This study addresses the lack of spatial planning and the suboptimal utilization of ecological, socio-cultural, and economic potentials in Lahan Carik, Cibodas Village, Bandung Regency. Although the area is a fertile highland region with distinctive agricultural traditions and community-based livestock systems, its development is hindered by limited infrastructure and tourism facilities. The objective of this study is to design an ecotourism concept that integrates environmental conservation, education, and recreation, while also empowering the local community through participatory planning. This research employs a qualitative method, with data collected through field observations, interviews, and literature review. The data is analyzed descriptively, focusing on environmental, socio-cultural, economic, and accessibility aspects. The findings indicate that the area possesses high biodiversity, traditional farming practices, strong cultural values, and scenic landscapes. However, it lacks organized spatial zoning, interpretive facilities, and sustainable infrastructure. The proposed concept includes functional zoning (conservation, production, recreation, water conservation, and buffer zones), educational trails, environmentally friendly circulation systems, and active community involvement in the management of agrotourism programs. Recommended facilities include a botanical garden, livestock waste processing area, composting unit, and a traditional farming demonstration zone, aimed at enhancing both ecological value and visitor experience. The discussion emphasizes the importance of aligning spatial design with the site’s ecological characteristics and local socio-economic context. In conclusion, the proposed design concept serves as a sustainable and participatory ecotourism framework that can revitalize Lahan Carik as an educational, ecological, and cultural destination, while providing benefits for both the environment and the local community.